Analisis Pelaksanaan Pembelajaran di SMAN 12 Kota Padang - Asagina Sabila; Nita Putri Utami (Algoritma : Jurnal Matematika, Ilmu pengetahuan Alam, Kebumian dan Angkasa, 2025)
This study aims to analyze the implementation of learning at SMAN 12 Padang City, especially in the preliminary activities, core activities, and closing activities carried out by mathematics teachers while the teacher is teaching in class. This study uses a qualitative descriptive approach with a descriptive design method. The research instruments used are interview guidelines, observation sheets, and documentation. Data collection techniques are carried out through interviews with subject teachers, direct observation of the learning process in class, and analysis of learning device documents such as teaching modules and semester programs. The results of the study indicate that the implementation of learning at SMAN 12 Padang City has been going quite well, marked by the implementation of learning components in accordance with the Merdeka Curriculum. Based on the results of observations, the implementation of the learning achieved a success percentage of 81.22% in grades X and XI. However, several obstacles were found such as limited time in preparing teaching devices optimally and variations in the use of learning media. This study is expected to be a material for evaluation and improvement in the management of the learning process in schools.